El acompañamiento familiar y la calidad de vida de los Adultos Mayores del Hogar de Ancianos Dr. Hugo Agila Vargas del cantón Paltas y la intervención del trabajador social - Guamán Pogo, Alvaro José (2020)
This research paper entitled "THE"THE FAMILY ACCOMPANIMENT AND QUALITY OF LIFE OF ADULTS MORE OF THE DR. HUGO AGILA VARGAS OF THE PALTAS CANTON AND THE INTERVENTION OF THE SOCIAL WORKER" contains some parameters that will allow explain in a clear way, the findings obtained in the research such as: abandonment, little affectivity and family care about the elderly, causing feelings of distress, depression, sadness, discomfort and inappropriate behaviors to feel the abandoned from their relatives, these being the causes that limit the biological, psychological and social well-being affecting the quality of life of the elderly. In addition, the specific objectives allowed in the investigative process to find different situations such as: the abandonment and lack of affectivity of their relatives that limit the well-being and quality of life in the elderly of the Nursing Home Dr. Hugo Agila Vargas. The reasons for older adults are because of the decision of their relatives, lack of financial resources, reasons for work and because there is no one to take care of them. It should be noted that family members do not provide adequate assistance in violation of the rights that the law grants to the older adult. For the development of the research, the methodology of the scientific, analytical, synthetic, inductive, deductive method that served to provide response and alternative solutions to the problem that was being investigated was used. With the help of quantitative and qualitative instruments and the techniques of observation, interview, survey and scale of GENCAT. The population is 13 older adults who are inmates in the institution, taking as a sample the 13 older adults, 13 family members and 5 members of the multidisciplinary team of the Home of elders Dr. Hugo Agila Vargas of Canton Paltas. Against this background, it is necessary to create a proposal for social intervention to strengthen the family's bonds of affectivity towards the elderly in the Home of the Elderly Dr. Hugo Agila Vargas of Canton Paltas, with the collaboration of their relatives and the staff working at the institution. Keywords: Family, Older Adult, Quality of Life.